Polyunsaturated fatty acids and membrane organization: The balance between immunotherapy and susceptibility to infection - Shaikh, Saame Raza (2008)
Polyunsaturated fatty acids (PUFAs), notably of the n-3 series, have immunosuppressive effects which make these molecules candidates for treating inflammatory symptoms associated with cardiovascular disease, obesity, arthritis, and asthma. However, immunosuppression by PUFAs could increase susceptibility to bacterial and viral infection. A detailed molecular picture is required in order to understand the balance between the benefits and risks of utilizing PUFAs as adjuvant immunosuppressants. Here we review evidence that incorporation of PUFAs into membrane lipids of antigen-presenting cells (APCs) downregulates APC function. We propose that PUFAs modulate antigen presentation by altering the organization of lipid and protein molecules of the plasma membrane and endomembranes; this alters recognition and responses by T cells. The foundation of our hypothesis is built on data from artificial bilayer experiments which provide the physical principles by which PUFA acyl chains affect membrane architecture. This review also reconciles conflicting results in the literature by discussing the advantages and disadvantages of differing methods of PUFA treatment of cells. We suggest that membrane modulation of immune cells may be an important and overlooked mechanism of immunomodulation. In addition, we propose that mechanistic studies with defined experimental protocols will speed the translation of laboratory studies on PUFAs to the clinic.